2017
DOI: 10.1002/pssr.201700029
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thermoelectric properties of Bi2Te3 and Sb2Te3 films grown on graphene substrate

Abstract: Phone: þ82 42 860 7677, Fax: þ82 42 861 4151A study of substrate effect on the thermoelectric (TE) properties of Bi 2 Te 3 (BT) and Sb 2 Te 3 (ST) thin films grown by plasma-enhanced chemical vapor deposition (PECVD) was performed. Graphene substrates which have small lattice mismatch with BT and ST were used for the preparation of highly oriented BT and ST thin films. Carrier mobility of the epitaxial BT and ST films grown on the graphene substrates increased as the deposition temperature increased, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Among the various thin film growth parameters, the T sub and the postannealing processing could remarkably alter the formation and transformation of atomic defects and thus the electronic transport properties of n-type Bi 2 Te 3 films. Our results [101] and the studies from other laboratories [81,92,132,133] have shown that the substrate temperatures T sub in the range of 240-350°C are suitable for the stable growth of highquality Bi 2 Te 3 films. Because the thermal evaporation temperature of Te is around 220°C, which is obviously lower than the optimal T sub , Bi 2 Te 3 films are generally grown under a Te-poor environment due to a serious re-evaporation of Te from the heated substrate.…”
Section: Atomic Defect Engineeringsupporting
confidence: 62%
See 3 more Smart Citations
“…Among the various thin film growth parameters, the T sub and the postannealing processing could remarkably alter the formation and transformation of atomic defects and thus the electronic transport properties of n-type Bi 2 Te 3 films. Our results [101] and the studies from other laboratories [81,92,132,133] have shown that the substrate temperatures T sub in the range of 240-350°C are suitable for the stable growth of highquality Bi 2 Te 3 films. Because the thermal evaporation temperature of Te is around 220°C, which is obviously lower than the optimal T sub , Bi 2 Te 3 films are generally grown under a Te-poor environment due to a serious re-evaporation of Te from the heated substrate.…”
Section: Atomic Defect Engineeringsupporting
confidence: 62%
“…As documented by the values of PF s from different groups, see Figure 3B, it is obvious that the optimized PF s in Bi 2 Te 3 films are in the range of 2.5–3.5 mWm –1 K –2 at T sub = 240–300°C. Measurements made by Lee et al [ 81 ] and Zhang et al [ 101 ] on single crystalline Bi 2 Te 3 films with the optimal carrier concentration of 7–9 × 10 19 cm –3 attained the highest PF of ∼3.5 mWm –1 K –2 . Similar to the effect of T sub , the annealing temperature ( T ann ) and the annealing time ( t ann ) during the postannealing process can also regulate atomic defects in Bi 2 Te 3 films.…”
Section: Strategies On Optimizing the Electronic Properties Of N‐type...mentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical vapour deposition (CVD) allows for the production of superior quality thin films with better conformity, coverage, and stoichiometric control compared with sputtering. Conventional deposition of binary or ternary compounds requires the use of multiple precursor systems [32], however recent work in single-source precursors (SSPs) is a promising alternative, allowing ease of handling and atom efficiency without compromising on stoichiometry or morphological control. We have previously demonstrated the viabilities of using SSPs to deposit high-quality binary (e.g.…”
Section: Introductionmentioning
confidence: 99%